Phenological patterns and their ecosystemic contribution of Ceiba speciosa (A. St.-Hil.) Ravenna and Koelreuteria paniculata Laxm. on the UNALM campus - Sangay-Tucto, Sheena (2024)
The present study aimed to evaluate dominant phenological patterns of Ceiba speciosa and Koelreuteria paniculata on the campus of UNALM, from May 2022 to June 2023, conducting weekly observations. Spearman’s correlation coefficient was utilized for statistical analysis, examining the relationship between climatic variables (temperature and relative humidity) and phenological events (flowering, fruiting, and leafing). The phenological assessment of both species was complemented with the identification of potential ecosystem services involved, employing the framework of Nature’s Contributions to People (NCP’s), classified into material, non-material, and regulatory categories. Results revealed a strong and highly significant association (p-value < 0.001) between flowering and flower drop in C. speciosa. For K. paniculata, fruit drop exhibited a significant association with dissemination and moderately significant association with leaf budding. Additionally, significant associations were observed between dissemination and leaf budding. Direction and degree of association were analysed at a significance level of 0.05 (p-value < 0.05). Identified NCP’s encompassed material services such as artisanal use of C. speciosa seeds and the biodiesel production potential from K. paniculata seeds. Moreover, non-material ecosystem services included regulation of pollination, photosynthesis, habitat maintenance, aesthetic value, and thermal regulation in urban environments. Finally, highlighting the interconnectedness between nature and human well-being underscores the imperative of understanding phenological patterns to maximize Nature’s Contributions to the well-being of the university community.